The Algorithm of Local Modulus Maximum Detection Based on B-spline Wavelet. Issue 4 (May 2019) - Jianwen, Zhao; Hou, Hui; Gao, Shupin
Abstract: At the time of fault, the system signal performances singularity, and the fault state can be diagnosed effectively through effective analysis and identification of singular signals. In this paper, for the problem that the singular signal modulus maximum point detection is inaccurate and the polarity is confused due to the improper selection of wavelet basis, the algorithm of local modulus maximum detection based on b-spline wavelet is proposed. B-spline scaling function is constructed by interpolation formula, the filter coefficients of b-spline wavelet function is calculated, in the process of signal decomposition of b-spline wavelet function and the effect of endpoint effect on signal singularity is removed, the signal local modulus maximum in the wavelet decomposition coefficient is extracted to accurately determine the time when the fault occurs. The result of simulation and experimental shows that the algorithm can not only detect the location of the maximum value of the singular point modulus accurately, but also distinguish the polarity of the modulus maximum and have good anti noise characteristics.